Theoretical study on the low-lying electronic excited states and laser cooling feasibility of AuH molecule. (February 2020) - Xu, Mao-Sen; Yang, Chuan-Lu; Wang, Mei-Shan; Ma, Xiao-Guang; Liu, Wen-Wang
Highlights: The optical laser cooling scheme is suggested for AuH. The cooling effect is evaluated with Einstein coefficient and recoil temperature. The potential energy curves of ten electronic states of AuH molecule are obtained. The spectroscopic parameters, the rovibrational energy levels are determined. The Franck–Condon and transition dipole moments are calculated for the states. Abstract: To evaluate characteristics of the low-lying electronic states and the feasibility of the laser cooling of the AuH molecule, we investigate the potential energy curves (PECs), the vibrational and rotational characteristics of the ground and low-lying excited electronic states based on ab initio calculations. The PECs of the X 1 Σ +, A 1 Σ +, B 1 Σ +, a 3 Σ +, b 3 Σ +, e 3 Σ +, C 1 П, D 1 П, c 3 П and d 3 П states and the transition dipole moments among these states are calculated with the multi-reference configuration interaction method with Davidson correction and all-electron basis sets. Based on the obtained PECs, the Schrödinger equations of nuclear movement are solved to obtain the rotational and vibrational energy levels of the electronic states. The spectroscopic parameters are obtained by fitting the obtained rotational and vibrational levels with Dunham series expansion. The matrices of the Franck-Condon factors (FCFs) dependent on the vibrational quantum numbers are obtained. The feasibility of laser cooling is explored. The FCF of the D 1 П ( v′  = 0) ↔ X 1 Σ + ( v″  = 0) transition is 0.9862, which implies that the AuH molecule is feasible but not the much better ones for laser cooling and more pumping lasers are needed. The optical laser cooling scheme is suggested and the Einstein coefficient and the recoil temperature are calculated to evaluate the effect of the cooling scheme.